Data as a Tradeable Commodity: Propertization vs. the Concept of Exclusive Rights - Filatova-Bilous, Nataliia (Teisė, 2022)
This article purports to determine the legal nature of data (personal data and nonpersonal data) and to find out which approach (propertization or exclusive rights theory) may be used to arrange the trade of data. It begins with the analysis of the notion of data and their various types and goes on to analyze modern concepts and theory explaining who the data may be attributed to and on which grounds data may be transmitted and acquired. In this context two theories are considered: a so-called theory of propertization of data and the theory of exclusive rights. Based on this analysis the approach to the legal determination of the legal nature of data and rights to them is introduced.
Keywords: personal data; Big data; masses of data; commodification of data; theory of propertization of data; property right